If we'll draw the graph of the function it will be a concave upward parabola. The vertex of parabola is aminimum point.

f(x) = 2x^2-7x+3

The area between the roots of quadratic is the area where parabola goes below the x axis. This area represents the solution of the inequality.

First, we'll determine the roots of the quadratic:

2x^2-7x+3 = 0

We'll apply the quadratic formula:

x1 = [7+sqrt(49 - 24)]/4

x1 = (7+sqrt25)/4

x1 = (7+5)/4

x1 = 3

x2 = (7-5)/4

x2 = 1/2

**The expression ****2x^2-7x+3 **** is negative when x belongs to the range (1/2 ; 3).**

2x^2-7x+3 < 0.

WE factorise the left to solve the inequality.

2x^2-6x-x+3 < 0

2x(x-3)-1(x-3) < 0

(2x-1)((x-3) < 0.So x= 1/2 and x = 3 are the zeros of the quadratic 2x^2-7x+3 .

So for **1/2 < x < 3**, LHS is negative .

first solve;

2x^2-7x+3 = 0

Only one of the solutions is less than 0.

This is your answer